Comparison of adjustable sutures versus nonadjustable sutures in intermittent exotropia. Issue 3 (May 2018) - , Kamlesh; Babu, Suresh; Goel, Yashpal; Chaudhary, Rupak Brahma; Rastogi, Anju; Agarwal, Richa; Dhiman, Shweta; Kumar, Prateek; Bharadwaj, Ankita
Purpose: To compare adjustable sutures versus nonadjustable sutures for intermittent exotropia. Methods: In this randomized prospective interventional study, 40 adult patients with intermittent exotropia were randomly divided into 2 equal groups. Both groups underwent bilateral lateral rectus recession. In group A, adjustable suture recession was performed, and in group B, nonadjustable suture recession was performed. Patients were followed up for 6 months and outcome measures were residual deviation, binocular status, and need for resurgery. Results: Success was defined as alignment of 2 eyes <10 prism diopters (PD) of deviation at the end of 12 weeks. Need for resurgery in a 12-week follow-up period was considered to be failure. At the end of the study, 90% of the patients in group A and 85% of the patients were within 10 prism diopters of orthophoria (p = 0.316). At the end of 6 months, mean deviation in group A was 6.20 PD and in group B it was 5.60 PD (p = 0.31). No patient underwent resurgery. Conclusions: Adjustable hang-back recession has no definite added advantage over nonadjustable hang-back recession in intermittent exotropia.